Carcinoembryonic Antigen: A Potential Biomarker to Evaluate the Severity and Prognosis of COVID-19 - Chen, Qianqian; Kong, Hui; Qi, Xu; Ding, Wenqiu; Ji, Ningfei; Wu, Chaojie; Huang, Chaolin; Wu, Wenjuan; Huang, Mao; Xie, Weiping; Liu, Yun; Tang, Jinhai (Frontiers in Medicine, 2020)
Background and Objectives: Corona Virus Disease 2019 (COVID-19) has become a serious pandemic disease worldwide. Identification of biomarkers to predict severity and prognosis is urgently needed for early medical intervention due to high mortality of critical cases with COVID-19. This retrospective study aimed to indicate the values of carcinoembryonic antigen (CEA) in evaluating the severity and prognosis of COVID-19. Methods: We included 46 death cases from intensive care unit and 68 discharged cases from ordinary units with confirmed COVID-19 of Wuhan Jin Yin-tan Hospital from January 1 to March 22, 2020. Laboratory and radiologic data were analyzed retrospectively. All patients were followed up until April 10, 2020. Results: COVID-19 patients in the death group had significantly higher CEA levels (ng/mL) than discharged group (14.80±14.20 vs 3.80±2.43, P<0.001). The risk of COVID-19 death increased 1.621 times for each additional 1 ng/mL CEA level. Receiver operating characteristic curve analysis suggested that the area under the curve of the serum CEA levels was 0.839 in discrimination between death cases and discharged cases with COVID-19 (P<0.001). Cutoff value of CEA levels was 5.3 ng/mL with a sensitivity of 76.7% and a specificity of 80.6%. Among discharged patients, CEA levels were significant lower in moderate cases compared to the severe cases (P<0.001) and critical cases (P=0.013). A positive correlation between CEA levels and CT scores existed in discharged patients (Correlation Coefficient: 0.687; P<0.001). Conclusions: Elevated CEA levels increased the risk of death from COVID-19 and CEA levels were related to CT scores of the discharged patients positively.